Firewalls jumpstart for network and systems administrators - Vacca, John R.; Ellis, Scott (Scott Raymond), 1968- (Amsterdam ; Boston : Elsevier Digital, 2005)
In this book, you will gain extensive hands-on experience installing and configuring a firewall. You will also learn how to allow access to key Web services while maintaining your organization's security, as well as how to implement firewall-to-firewall virtual private networks (VPNs). You will learn how to build a firewall to protect your network; provide access to HTTP and FTP services on the Internet, and implement publicly accessible servers without compromising security. Furthermore, throughout the book, extensive hands-on examples provide you with practical experience in establishing security with firewalls. Examples include, but are not limited to: Installing and configuring Check Point FireWall-1; scanning to validate configuration using ISS Internet Scanner; configuring the firewall to support simple and complex Web services; setting up a packet filtering router; enhancing firewall configurations to support split-DNS; authenticating remote users; and protecting browsers and servers with a proxy-based firewall. Install and configure proxy-based and stateful-filtering firewalls Protect internal IP addresses with NAT and deploy a secure DNS architecture Develop an Internet/intranet security policy to protect your organization's systems and data Reduce your susceptibility to an attack by deploying firewalls, data encryption and decryption and other countermeasures.
Firewalls : what are they? -- Type of firewall security policy -- Firewall types -- Choosing the right firewall -- Defense in depth : firewall topologies -- Installation preparation -- Firewall configuration -- Simple policy implementation -- Complex web services management -- Content filtering -- Publicly accessible servers implementation -- Architecture selection -- External servers protection -- Internal IP security threats : Beyond the firewall -- Network address translation deployment -- Privacy and authentication technology -- Tunneling : firewall-to-firewall -- Auditing and logging -- Firewall administration.
Includes bibliographical references and index.
Keywords: Firewalls (Computer security); Electronic books